2018
DOI: 10.1080/00207543.2018.1458165
|View full text |Cite
|
Sign up to set email alerts
|

Balancing modularity and solution space freedom: effects on organisational learning and sustainable innovation

Abstract: Many technology-intensive (TI) firms find it challenging to leverage customisation and achieve sustainable innovation. Although some firms use modularity to tackle this challenge, mixed effects on sustainable innovation have been reported. This study uses organisational learning and ambidexterity theory to provide insights into how TI firms can achieve 'winwin' situations where sustainable innovation is increased through customisation. First, we argue that customisation should be viewed two-dimensionally and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 117 publications
0
22
0
5
Order By: Relevance
“…Firms can then gain a near-monopoly advantage in their industries (Fixson and Park, 2006). However, they may need to balance the use of MD with an appropriate level of freedom in the solution space (Vos et al , 2018), with effective strategic learning (Salonen et al , 2018) or with an innovation strategy (Bouncken et al , 2015). Finally, further comprehensive studies should be conducted to examine the diminishing effects of MD on product innovation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firms can then gain a near-monopoly advantage in their industries (Fixson and Park, 2006). However, they may need to balance the use of MD with an appropriate level of freedom in the solution space (Vos et al , 2018), with effective strategic learning (Salonen et al , 2018) or with an innovation strategy (Bouncken et al , 2015). Finally, further comprehensive studies should be conducted to examine the diminishing effects of MD on product innovation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lau et al (2011) argue that pursuing both modular and innovative products may be counterproductive, and the critical factors in creating MD have not been fully identified. Vos et al (2018) find that MD and freedom in terms of design solutions must be aligned to ensure effective organisational learning and new product performance (NPP). In general, MD is important for successful product innovation as it helps motivate developers to create new products using a trial and error approach (Ulrich and Eppinger, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste sentido, Quandt, Ferraresi e Bezerra (2017) propõem um modelo que associa o desempenho inovador a dez dimensões de inovatividade organizacionais, a saber: (1) estratégia, responsável por explicitar o papel da inovação no contexto geral (BAUM; LOOF; NABAVI, CANDI, et al, 2018;SCHIAVI;BEHR, 2018) MEMON, 2019;VOS, et al, 2018;CARVALHO, et al, 2017).…”
Section: Inovatividade E Desempenho Inovadorunclassified
“…Most studies suggested that PM can promote PI (e.g. Baldwin and Clark, 1997; Hao et al , 2015; Lau et al , 2010; Mikkola, 2000; Vickery et al , 2016; Vos et al , 2018; Wang et al , 2016). Studies have found that PM can improve efficiency (Barbosa et al , 2017; Piran et al , 2016) and increase launch speed of new product (Vickery et al 2016).…”
Section: Introductionmentioning
confidence: 99%